1998
DOI: 10.1152/ajpregu.1998.275.5.r1712
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meal volume and posture on gastric emptying of solids and appetite

Abstract: The effects of volume and posture on gastric emptying and intragastric distribution of a solid meal and appetite were evaluated. Eight normal volunteers were studied on four occasions, on each of which a meal comprising ground beef mixed with tomato sauce of either 650 g (“large”) or 217 g (“small”) was eaten. Two studies were performed while the subject was lying in the left lateral decubitus position, and two studies were performed while the subject was sitting so that in each subject data were available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 20 publications
3
62
0
1
Order By: Relevance
“…In contrast, Spiegel et al found no posture-dependent differences in postprandial hunger after the ingestion of soup and a sandwich (seated vs. supine), which they explained by a different meal composition and a shorter observation period (0-120 min post-ingestion) [12]. After the ingestion of a solid meal (without liquid component), no statistical significant difference in satiety ratings for sitting and left lateral position could be observed [10].…”
Section: Posture and Appetitementioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, Spiegel et al found no posture-dependent differences in postprandial hunger after the ingestion of soup and a sandwich (seated vs. supine), which they explained by a different meal composition and a shorter observation period (0-120 min post-ingestion) [12]. After the ingestion of a solid meal (without liquid component), no statistical significant difference in satiety ratings for sitting and left lateral position could be observed [10].…”
Section: Posture and Appetitementioning
confidence: 93%
“…In terms of the effects of posture on the gastric emptying of solid food, conflicting results have been published. Whereas Asada et al [9] found gastric emptying to be more delayed in the supine position versus the sitting position, Doran et al did not see any relevant influence of posture (left lateral vs. sitting) following the administration of both a small and a large meal [10]. Doran et al concluded that posture has only a minor influence on intragastric distribution and no effect at all on gastric emptying of solid food.…”
Section: Effects Of Posture On the Gastric Residence Time Of Fluids Amentioning
confidence: 99%
“…Reporting medical centers have often developed their own techniques. Because technique, especially the composition of the test meal (16,18,32,74), may significantly influence observed gastric emptying, published normal values cannot be easily compared. In a recent multicenter study, Tougas et al (71,72) used a standard homogenized egg substitute which was similar in properties to eggs.…”
Section: Measurement Of Gastric Emptying By Gamma Scintigraphymentioning
confidence: 99%
“…H o w e v e r , t h e r e i s n o a g r e e m e n t a m o n g t h e i r experimental results. Asada et al (1989) and Moore et al (1988) reported an association between postprandial sitting position and the faster gastric emptying of solid meals, but Doran et al (1998) showed that the major effect of meal volume had a greater effect on gastric emptying than postprandial posture.…”
Section: Introductionmentioning
confidence: 99%